Convalescent plasma therapy for COVID-19: a review of old therapy against new disease - Chapagain, Utshav; Raunair, Gajendra Prasad; Chapagain, Kumud; Verma, Rakesh (International Journal of Basic & Clinical Pharmacology, 2020)
Currently, novel coronavirus disease 2019 (COVID-19) is a big threat to global health which has revived the potential beneficial effect of ancient convalescent plasma therapy (CPT). This review was conducted to evaluate the effectiveness and adverse drug reactions associated with convalescent plasma therapy in COVID-19 patients, based on articles available to date. PubMed, Google Scholar, Cochrane library, and Hinari databases were searched until 15th September 2020. Every country across the globe today is encountered with a virus that has impacted millions of lives today and for generations to come. Nonetheless recommended antiviral drugs and vaccines are not evident and specified for novel coronavirus disease. This is now very well known that scientists and medical experts across the world are vigilant about recommending the use of CPT and call it an investigational treatment that may help in assisting recovery. The World health organization has perpetuated that there is not enough proof that plasma therapy works in treating those fighting the novel coronavirus. Therefore, convalescent plasma therapy is a feasible and immediate option for alleviating the impact of the disease. Comparing the effectiveness of convalescent plasma therapy with SARS-CoV, MERS-CoV, and COVID-19 would help in deriving proper outcomes for COVID-19 infected cases.